Population structure analysis and construction of DNA fingerprinting in eggplant (Solanum melongena L.) based on whole-genome resequencing - Ruining Lai; Chuan Zhong; Jiechun Peng; Kongxiu Su; Duoduo Xiao; Bingying Zou; Meimei Shi; Jingjing Huang; Huarong Fang; Jinling He; Xinyuan Chen; Junwei Zhang; et al. (Genetic Resources and Crop Evolution, 2026)

Hybrid vesicle-camouflaged cascade nanoreactors enable dual-targeted ferroptotic killing of intracellular MRSA and immune remodeling in pneumonia - Siyuan Yu; Yueru Pang; Ziqi Shen; Feiyang Liu; Ruixin Kang; Wei Li; Ruining Li; Lin Luo; Junyan Zhang; Qi Shen (Chemical Engineering Journal, 2026)

Advances in targeted nutrient delivery: materials design and mechanistic perspectives for precision nutrition - Yi Wang; Guannan Liu; Ruining Zhang; Yaqiong Wang; Pei Wang; Chong Xie; Hansong Yu; Runqiang Yang (Food Research International, 2026)

Ultraviolet-treated riboflavin induces ROS-mediated apoptosis via inhibiting mitochondrial complex I in acute myeloid leukemia - Ruining Liu; Shuang Ge; Jinyuan Sun; Yi Liu; Liping Sun; Yang Yu; Deqing Wang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Citric acid modification of insoluble dietary fiber from soybean residue: Microstructural reconstruction, interfacial activity enhancement and stability by pickering emulsions - Ziyue Yu; Yuting Yang; Ying Zhang; Ruining Zhang; Bo Lyu; Sainan Wang; Wendan Jing; Hansong Yu (Food Research International, 2025)

Soybean insoluble Fiber-EGCG binary compounds: Enhanced stability and synergistic antioxidant activity - Yi Wang; Ruining Zhang; Shidi Men; Mingzhe Li; Guannan Liu; Xiangbo Zeng; Bo Lyu; Sainan Wang; Hansong Yu (Food Chemistry, 2025)

Dual-channel NIR self-illuminating nanoprobe for high-contrast imaging of reactive oxygen species in vivo - Hao Yuan; Hong Hu; Shengchun Sun; Jianxing Feng; Ning Shi; Yong Qiu; Ruining Yu; Yixian Wang (Chemical Engineering Journal, 2025)

Long-term soy dietary fiber diet modifies the intestinal internal environment: Focus on chronic ulcerative colitis - Yi Wang; Ruining Zhang; Mingzhe Li; Jiaxin Li; Guannan Liu; Sainan Wang; Bo Lyu; Hansong Yu (Food Research International, 2025)

Augmentation of antiviral immune response induced by perturbation of CD82 under microgravity condition - Yuzhi Zhang; Sijie Wang; Jiawei Chen; Yidan Zhou; Xiaoyu Yu; Ruining Peng; Longfeng Lu; Shun Li; Zhenhao Tian; Nu Zhang; Hui Yang (Fish & Shellfish Immunology, 2025)

Effects of Glutamate on Growth Performance, Gut Digestion and Antioxidant Capacity in Juvenile Little Yellow Croaker - Ruining Liu; Yu Zhang; Xiao Liang; Bao Lou; Junquan Zhu (Fishes, 2025)
This study is to explore the alleviating effects of glutamate on intestinal damage in cultured little yellow croaker. A total of 900 juvenile fish at a weight of 30.68 ± 0.12 g were randomly separated into six groups with three replicates each, and were fed a basic diet (protein at 44.42% and lipid at 12.48%) with additional glutamate at 0.00%, 0.40%, 0.80%, 1.2%, 1.60%, and 2.00%. Each replica group consisted of 50 fish in a breeding barrel (radius 1.0 m, height 1.5 m), and the experiment lasted for 54 days. The results showed that supplementation with 0.4–1.2% glutamate significantly improved the survival rate, which increased from 75.56% to 91.11%, reduced the feed conversion rate from 1.75 to 1.57, and increased the protein efficiency ratio from 1.55 to 1.85 (p

Global assessment of radiative cooling and low-emissivity coatings for energy efficiency in buildings across all climate zones - Jiashuo Wang; Zekai Li; Tongyu Zhou; Wu Deng; Runqi Liang; Isaac Yu-Fat Lun; Yilin Li; Ruining Bao (Energy and Buildings, 2024)

Priority bacteria causing biofouling of reverse osmosis membranes: Potential disinfection-resistant bacteria and control strategies - Yujia Gao; Haobin Wang; Yuqing Xu; Ruining Wang; Han Liu; Yu Qiu; Yu Hong; Hongying Hu; Yinhu Wu (Desalination, 2024)

The development process of plant-based meat alternatives: Raw material formulations and processing strategies - Yi Wang; Bo Lyu; Hongling Fu; Jiaxin Li; Lei Ji; Hao Gong; Ruining Zhang; Jingsheng Liu; Hansong Yu (Food Research International, 2023)